The SL(2,R) Group Representations on Spaces of Holomorphic Functions on the Unit Disc (European Journal of Pure and Applied Mathematics, 2023)
We can realise the representations of the group SL(2,R) on the unit disc. This is due to an isomorphism between the group SL(2,R) and the group SU(1,1). The discrete series representations for the group SL(2,R)given byπ_{n}(g)φ(z)=φ (\frac{d z-b}{a-cz} )(a-c z)^{-n}, where n is an integer number,is on the Bergman space where n>2 .Lang studies the discrete series on the group in the upper half-plane and on the unit disc. For n=1, the SL(2,R) representation is called the mock discrete series. The representation space of the mock discrete series is the Hardy space.In this article we describe the SL(2,R) representation on the Dirichlet space.
Keywords: Representation; SL_2(R); SU(1 .1); Dirichlet space